2004
DOI: 10.4049/jimmunol.172.7.4275
|View full text |Cite
|
Sign up to set email alerts
|

Smad3 Is Essential for TGF-β1 to Suppress IL-2 Production and TCR-Induced Proliferation, but Not IL-2-Induced Proliferation

Abstract: Transforming growth factor-β1 is essential to maintain T cell homeostasis, as illustrated by multiorgan inflammation in mice deficient in TGF-β1 signaling. Despite the physiological importance, the mechanisms that TGF-β1 uses to regulate T cell expansion remain poorly understood. TGF-β1 signals through transmembrane receptor serine/threonine kinases to activate multiple intracellular effector molecules, including the cytosolic signaling transducers of the Smad protein family. We used Smad3−/− mice to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
93
0
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 58 publications
9
93
0
2
Order By: Relevance
“…We first confirmed that while Smad3 -/-CD4 + T cells are as susceptible to suppression by CD4 + CD25 + T cells as WT CD4 + T cells in vitro, they are resistant to the suppressive effects of TGF-b1, as they actively transcribe the IL-2 gene and proliferate following TCR stimulation in the presence of exogenous TGF-b1 (Fig. 4a) [27]. We next analyzed the role for Smad3 in our colitis model.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…We first confirmed that while Smad3 -/-CD4 + T cells are as susceptible to suppression by CD4 + CD25 + T cells as WT CD4 + T cells in vitro, they are resistant to the suppressive effects of TGF-b1, as they actively transcribe the IL-2 gene and proliferate following TCR stimulation in the presence of exogenous TGF-b1 (Fig. 4a) [27]. We next analyzed the role for Smad3 in our colitis model.…”
Section: Resultssupporting
confidence: 61%
“…A second aspect of our studies was to determine the target cell for the immunosuppressive effects of TGF-b in our model of IBD. We first explored the possibility that TGF-b acts on the CD4 + CD25 + Treg cells themselves, as it has been shown that the production of this cytokine by islet cells during the priming phase of diabetes protects mice from disease and increases the number of intraislet CD4 + CD25 + T cells [27]. Furthermore, CD4 + CD25 + T cells from mice expressing a dominant negative form of TGF-bRII failed to expand in vivo and to suppress dextran sulfate sodium-induced colitis [31].…”
Section: Discussionmentioning
confidence: 99%
“…Differently from PKCu, the overexpression of PKCε reduced Smad2, but not Smad3, phosphorylation. In line with previous data, demonstrating that both Smad2 and Smad3 contribute to TGF-1b-induced inhibition of IL-2-sustained T cell proliferation (43), it looks reasonable that pSmad2 is downstream PKCε signaling. However, because it is well-known that addition of IL-2 can override the growth arrest of T cells mediated by TGF-1b (10), we cannot exclude that the ability of PKCε to regulate IL-2R expression levels might also explain the increased TGF-1b sensitivity of siRNA PKCε -transfected cells.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, it is known that TGF inhibits IL-2 and anti-CD3/CD28-induced T cell proliferation in a Smad3-dependent manner. By contrast, Smad3 is not essential for TGF-1b-mediated inhibition of IL-2-induced T cell proliferation of lymphocytes activated by ConA (43). Looking for TGF-1b signaling intermediates potentially targeted by PKCε, we analyzed pSmad2 and pSmad3 levels in PKCε-overexpressing Jurkat cells and in primary activated CD4 cell cultures treated with TGF-1b for 2 h. Of note, PKCε overexpression significantly reduced TGF-1b-induced pSmad-2 levels in Jurkat cells (Fig.…”
Section: Pkc« Impaired Tgf-1b Signalingmentioning
confidence: 84%
“…We showed above that TGF-b also suppressed the proliferation of gd cells. We propose that TGF-b targets, on the one hand, the endogenous IL-2 production of TCRVg9 + T lymphocytes presumably through blockade of its gene promoter as in ab T lymphocytes (64,65) because exogenous IL-2 partially reversed this blockade. On the other hand, TGF-b inhibited the functions induced by TCR signaling, but this was reversed by increasing doses of PAg stimulus.…”
Section: Discussionmentioning
confidence: 99%